Desensitization with plasma exchange in a patient with human leukocyte antigen donor‐specific antibodies before T‐cell–replete haploidentical transplantation. Issue 5 (28th March 2016) - Bramanti, Stefania; Nocco, Angela; Mauro, Elisa; Milone, Giuseppe; Morabito, Lucio; Sarina, Barbara; Crocchiolo, Roberto; Timofeeva, Inna; Capizzuto, Rossana; Carlo‐Stella, Carmelo; Santoro, Armando; Castagna, Luca
Abstract : BACKGROUND: The presence of human leukocyte antigen donor‐specific antibodies (DSAs) increases the risk of graft failure in T‐cell–replete haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) CASE REPORT: A 49‐year‐old female with high‐risk acute myeloid leukemia in first complete remission received a haplo‐HSCT from her daughter. Pretransplant recipient screening examination showed high DSAs levels against unshared class I leukocyte antigens. RESULTS: The patient underwent a desensitization program consisting of plasma exchange (PEX), polyvalent intravenous (IV) immunoglobulins, and IV tacrolimus and mycophenolate mofetil (MMF). This protocol resulted in the disappearance of the DSA anti HLA B41. Engraftment was prompt with stable full donor chimerism. CONCLUSIONS: This case report suggests that the adopted scheme is safe for reducing DSA levels and facilitating donor engraftment in patients scheduled for haplo‐HSCT.